Estimating the prevalence of any impairing childhood mental disorder in the national health interview survey. Issue 4 (23rd July 2015) - Ringeisen, Heather; Aldworth, Jeremy; Colpe, Lisa J.; Pringle, Beverly; Simile, Catherine
Abstract: This study investigates whether the six‐item Strengths and Difficulties Questionnaire SDQ (five symptoms and one impact item) included in the National Health Interview Survey (NHIS) can be used to construct models that accurately estimate the prevalence of any impairing mental disorder among children 4–17 years old as measured by a shortened Child/Adolescent or Preschool Age Psychiatric Assessment (CAPA or PAPA). A subsample of 217 NHIS respondents completed a follow‐up CAPA or PAPA interview. Logistic regression models were developed to model presence of any child mental disorder with impairment (MDI) or with severe impairment (MDSI). Models containing only the SDQ impact item exhibited highly biased prevalence estimates. The best‐performing model included information from both the five symptom SDQ items and the impact item, where absolute bias was reduced and sensitivity and concordance were increased. This study illustrates the importance of using all available information from the six‐item SDQ to accurately estimate the prevalence of any impairing childhood mental disorder from the NHIS. Copyright © 2015 John Wiley & Sons, Ltd.